Group piano mapping in brazilian higher education (Orfeu, 2016)
This study aims to contribute to theknowledge about the history and expansion of Group Piano in Brazil. Keeping in mind that in this methodology there is an interconnection of both musical languages, theory and musicianship, and in a collective manner. Therefore, in higher education institutions this approach of applied theory makes use of various digital pianosor keyboards collectively and it is usually referred to as Group Piano. However, inBrazil, the absence of a more updated and complete information on a national level about the presence of this course at the undergraduate music curriculum challenges research, specially due to the many different denominations it receives. This study presents some basic historic characteristics about this methodology and confirms its presence in Brazil through a national survey.
Keywords: Brazilian Universities; Group Piano; Group Music Teaching; Secondary Piano Skills